What and why is the "evolutionary scale" in Swiss Animal Welfare Law? Putting the Platypus in its Place - Kirsten Persson; Christian Rodriguez Perez; Sebastian Hartstang; Peter Kunzmann; Bernhard Hiebl; David Shaw (Journal of Animal Law, Ethics and One Health)
In the Swiss Animal Welfare Law, paragraph 20 (2) specifically requires the selection of those animal species for experiments that are “lower on the evolutionary scale”. From a biological perspective, however, the idea of an evolutionary scale is clearly outdated. In this bioethical article we will (1) analyse the potential meaning of the “evolutionary scale paragraph” in the Swiss Animal Welfare Law, (2) shed light on the consequences for animal model selection in animal research and (3) critically discuss alternative approaches to the regulation of animal model selection, including the suggestion of a case-by-case approach. Shifting from general species-specific animal properties such as the ability to feel pain to study-specific aspects such as being harmed by living in isolation or by being handled by humans in a particular way could lead to criteria that promote a selection of animal models that differs to some extent from the current research practice. Empirical data on the implementation of such animal welfare-related criteria in the actual planning of a study are, however, lacking.